Advanced glycation end products and risk of mortality in patients with cirrhosis: a prospective cohort study - Mohsen Shaygan Tabar; Maryam Nilghaz; Azita Hekmatdoost; Fereshteh Pashayee-Khamene; Zeinab Mokhtari; Sara Karimi; Saleheh Ahmadzadeh; Mehdi Saberifiroozi; Behzad Hatami; Zahra Yari (Scientific Reports)
Abstract The role of diet in reducing the burden of liver disease and mortality attributed to cirrhosis is very imperative. The present study scrutinized the relationship between dietary advanced glycation end products (AGEs) and mortality in patients with cirrhosis. This research was a prospective cohort study on 166 ambulatory cirrhotic patients who had been diagnosed with cirrhosis for a maximum of six months. Follow-up of patients continued for 5 years until May 2024. To determine the incidence of mortality in the quartiles of dietary AGEs, cox regression models were used with the adjustment of potential confounding variables. Although the first model of the analysis by adjusting the results for age and sex failed to show a significant increase in the risk of mortality in patients (HRQ4 vs. Q1 = 2.64; 95% CI = 0.9–7.5, P trend = 0.075), after adjusting the results for further confounders in the second (HRQ4 vs. Q1 = 3.56; 95% CI = 1.1–11.6, P trend = 0.040) and third (HRQ4 vs. Q1 = 3.3; 95% CI = 1.79–13.7, P trend = 0.048) models, the P trend for the risk of mortality during the quartiles of AGEs became significant. In addition, along with increasing trend of dietary AGEs, the number of deaths increased significantly (P = 0.024). Higher mortality risk was generally attributed to higher dietary AGEs in patients with cirrhosis.